NASIONALISME LOKAL ELITE JAWA TIMUR DALAM KRISIS PEMERINTAHAN RI 1948 â 1950 - Sapto, Ari (Jurnal Sejarah dan Budaya, 2010)
Abstract: Elite in the revolutionary process occupies an important role. The position of the elite is increasing in accordance with its ability to prove beneficial to the community. Elite East Java using local values as a reference in looking at one episode in the development of the Indonesian National Revolution is agovernment crisis. Elite East Java also has its own views about the struggle for independence. Application of the principles adopted by the cause of competition with other elites, especially the elite of the communist group of national and state.